2022
DOI: 10.3389/fonc.2021.758509
|View full text |Cite
|
Sign up to set email alerts
|

Early Postoperative Serum Carcinoembryonic Antigen Is a Stronger Independent Prognostic Factor for Stage II Colorectal Cancer Patients Than T4 Stage and Preoperative CEA

Abstract: BackgroundSerum carcinoembryonic antigen (CEA) is an important biomarker for diagnosis, prognosis, recurrence, metastasis monitoring, and the evaluation of the effect of chemotherapy in colorectal cancer (CRC). However, few studies have focused on the role of early postoperative CEA in the prognosis of stage II CRC.MethodsPatients with stage II CRC diagnosed between January 2007 and December 2015 were included. Receiver operating characteristic (ROC) curves were used to obtain the cutoff value of early postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
7
0
2
Order By: Relevance
“…Serum carcinoembryonic antigen (CEA) is one of the established biomarkers for diagnosis, monitoring the recurrence and metastasis and the evaluation of chemotherapy in CRC [ 35 , 36 ]. Recently, the prognostic impacts of CEA have been evaluated by using ROC curves and reported that post-operative CEA (AUC = 0.686, 95% CI = 0.657–0.714) was better than pre-operative CEA (AUC = 0.621, 95% CI = 0.592–0.650) in stage II CRC [ 35 ]. In the present study, the ROC curve revealed that AUC of SPATA18 was 0.595 (95% CI = 0.50–0.69; Figure 2 a).…”
Section: Discussionmentioning
confidence: 99%
“…Serum carcinoembryonic antigen (CEA) is one of the established biomarkers for diagnosis, monitoring the recurrence and metastasis and the evaluation of chemotherapy in CRC [ 35 , 36 ]. Recently, the prognostic impacts of CEA have been evaluated by using ROC curves and reported that post-operative CEA (AUC = 0.686, 95% CI = 0.657–0.714) was better than pre-operative CEA (AUC = 0.621, 95% CI = 0.592–0.650) in stage II CRC [ 35 ]. In the present study, the ROC curve revealed that AUC of SPATA18 was 0.595 (95% CI = 0.50–0.69; Figure 2 a).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that a high-normal preoperative CEA level was an independent prognosticator for poor DFS in CRC compared with the low-normal group. 33,34 However, Fenqi et al 35 showed that when the early postoperative CEA level was positive (>3.66 ng/mL) in patients with stage II CRC, the preoperative CEA level showed no significant effect on the patient’s prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…By multivariate analyses, elevated baseline level of CA19-9, advanced pN stage and harvested lymph nodes less than 12 were found to be independently associated with DM, and the first two were also independent prognostic factors for DFS, whereas advanced pN stage was associated with poor CSS. It is known that many tumor markers, such as CEA and CA19-9, are useful prognostic indicator to predict relapse and survival in rectal cancer patients ( 23 25 ). In addition to the association between baseline CA19-9 level and DM after laparoscopic resection of rectal cancer, our study showed that elevated baseline level of CEA was an independent risk factor for lung metastasis and predicted inferior DFS.…”
Section: Discussionmentioning
confidence: 99%